Tumor-to-tumor metastasis: Warthin tumor as a recipient of lung carcinoma and of renal carcinoma - Report of two cases - Laco, Jan; Celakovsky, Petr; Kalfert, David; Hornychova, Helena; Rybnikar, Tomas; Ryska, Ales (Pathology, research and practice, 2010)
Tumor-to-tumor metastasis is an exceedingly rare event with only about 100 cases reported in the English written literature. We report two cases of a 65-year-old man with duplicity of colonic and lung adenocarcinomas who presented with swelling of the left parotid gland, and of a 75-year-old man who presented with swelling of the right parotid gland. Microscopical and immunohistochemical examination showed metastasis of lung carcinoma and of renal carcinoma, respectively, to Warthin tumor as the first clinical manifestation of the malignancy in the latter case. To the best of our knowledge, such a phenomenon has not been reported so far.
Keywords: Parotid Neoplasms; adenolymfom; nádory plic; lidé; karcinom z renálních buněk; Kidney Neoplasms; Carcinoma, Renal Cell; Neoplasms, Multiple Primary; Adenocarcinoma; Male; Aged; nádory příušní žlázy; adenokarcinom; mnohočetné primární nádory; Lung Neoplasms; nádory ledvin; senioři; mužské pohlaví; Adenolymphoma; Humans